Thermoplastic and thermosetting composites with natural fibers - Mulinari, Daniella R.; Saron, Clodoaldo; Carvalho, Kelly C.C. [UNESP]; Voorwald, Herman J.C. [UNESP] (My University, 2011)
Nowadays, great attention has been dedicated to the development of natural fiber reinforced composites. Natural fibers provide with interesting properties the final composite, especially those related to environment the protection such as their capacity to be recyclable, renewable raw material, and less abrasive and harmful behavior. Some advantages associated to the use of natural fibers as reinforcement in plastics are their non-abrasive nature, biodegradability, low energy consumption, low cost, low density and high specific properties. The specific mechanical properties of natural fibers are comparable to those of traditional reinforcements. However, certain drawbacks such as incompatibility with a hydrophobic polymer matrix, the tendency to form aggregates during processing and poor resistance to moisture greatly reduce the potential of natural fibers to be used as reinforcement in polymers. On the other hand, various treatments are being used to improve fiber-matrix compatibility. This process is considered critical as development phase of these materials due to strong interfiber hydrogen bonding, which holds the fibers together. Methods for surface modification can be physical or chemical according to superficial modification approach of the fiber. Others frequently used treatments are bleaching, acetylation and alkali treatment. In this chapter, the main results presented in the literature are summarized, focusing attention on the properties in terms of physical and chemical structure of natural fibers, thermal and mechanical properties, processing behavior and final properties of natural fibers with thermoplastics and thermosetting matrixes paying attention to the use of physical and chemical treatments for the improvement of fiber-matrix interaction. ©2011 Nova Science Publishers, Inc. All rights reserved.